Allometric models for estimating aboveground biomass and carbon stock in planted aquilaria malaccensis stand - Jalil, Abd Majid; Abdul Hamid, Hazandy; Mohamad Ali, Nor Azah; Mohamed, Johar (Forest Research Institute Malaysia, 2021)
In Malaysia, the demand for high-value agarwood produced by Aquilaria spp. and efforts to reduce harvesting pressure on wild stands of these trees have resulted in an increase of Aquilaria plantations, which are harvested as a short-rotation (7 years) tree crop. Aquilaria spp. plantations potentially contribute to biomass accumulation as the trees are planted as reforestation and afforestation projects on marginal and idle lands but harvesting may affect their function as carbon sink. There are important environmental impact assessments of Aquilaria spp. plantations related to biomass and carbon sequestration. This study was conducted to develop an allometric model to estimate aboveground biomass and carbon stocks for plantation-grown Aquilaria spp. A census was conducted on 418 ten-year-old Aquilaria malaccencis trees on a 1-ha plot and measurements of height and stem diameter were used to categorise the trees into three diameter classes (small, medium, large). Ten trees were randomly selected for destructive sampling and developing allometric equations for estimating aboveground biomass. The recommended model, which used stem diameter as the predictor variable, estimated 23,615 kg total aboveground biomass for this 1-ha plot. Carbon analysis of stem, branches and foliage revealed an average carbon content of 40.35%. Average carbon density was 285 kg tree-1 and 9353 kg ha-1. The 10 destructively sampled trees stored 1046 kg CO2 equivalent. Our findings provided baseline information on the biomass and carbon stock measurements for plantation-grown A. malaccensis and supported plantation in accumulating biomass and carbon storage.